The Value of the chest X-Ray for diagnosing left ventricular Dysfunction - Shareef, Layth R.; AL- Doori, Kasim M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: The use of the chest x-ray measurements which includes the cardiothoracic ratio(C-T) and frontal area (FA) of the heart by the CXR are useful measures for primary assessment of the cardiac dysfunction. Patients and Methods: A Prospective study was done from the 1st of January 2005 to the 1st of October in the same year on a 120 consecutive patients who have been admitted for coronary and L.V angiogram at IBN-AL-BITAR hospital. The C-T ratio and the frontal area were measured. Results: The study comprised 120 subjects who were admitted for coronary and L.V angiogram for diagnostic reasons. 89subjects (74.2%) are male and 31subjects (25.8%) are female .17(14%) subjects have left ventricular dysfunction and dilated L.V with EDV≥110 cm^2 by angiogram. (76) Subjects (71%) had LAD (Left anterior descending artery disease), (40) subjects (37%) had LCX (Left circumflex artery disease), 10subjects (9%) had LMS (Left main stem artery disease) and (38) subjects (34%) RCA (disease). 13subjects (10%) had valve disease , 2subjects (1%) of them have aortic stenosis , 5 subjects (4%) had A.I (aortic inche), 4 subjects (3%) had M.S(Mitral stenosis) , 6 subjects (5%) had M.R Mitral regurgitation and combined valve disease .The abnormal chestradiogram C/T Ratio had a sensitivity of 56.6%, a specificity of 78.6%, and positive ,negative predictive values and accuracy of 95.2% ,19.3% and 59.2% respectively, in the diagnosis of left ventricular dysfunction.while the abnormal chest radiogram FA/BSA £ had a sensitivity of 47.2%, specificity of 42.9%, and positive ,negative predictive values and accuracy of 86.2% ,9.7% and 46.7% respectively. Conclusion: The radiological study of the thorax is not an accurate indicator of left ventricular dysfunction; its use as a screening method to initially approach the patient with ventricular dysfunction should be reevaluated.